44 Tiling array shows low ANRIL, high CDKN2B expression associated with chromosome 9p21 coronary artery disease (CAD) risk genotype. Issue 20 (23rd September 2011) - Beeton, L D; Chivers, P; Dawes, J; Kyriakou, T; Goel, A; Peden, J; Green, F R
Abstract : Recent studies suggest that ANRIL expression mediates susceptibility to CAD1 via CDKN2B.2 We used fluorescently-labelled whole-blood RNA, from 20 healthy volunteers genotyped for the CAD-risk-SNP rs2891168, to probe custom-designed Agilent tiling expression microarrays. Raw data were normalized to probe GC content and housekeeping genes. We found that ANRIL exons 1–4 were more abundantly expressed in blood than 5–20, with exons 6, 8, 9, 20 showing low expression. We derived a set of "training" tiling probes from HUVEC cells in which ANRIL expression was attenuated using siRNA against exons 13 and 19. ANRIL expression (probes in exons 5, 6, 8, 13, 16, 18, 19) was reduced by at least 50% and CDKN2B expression (probes in exons 1, 2) increased, with no effect on CDKN2A. We confirmed these data using real-time QPCR. Using the tiling probe "training-set", a probe in exon 16 of ANRIL showed a CAD genotype-specific difference in expression (p<0.001), with the risk-allele lower, and probes in exon 2 of CDKN2B showed higher expression for the risk-allele (p<0.05 and p<0.01). In conclusion, we found by a novel technique that ANRIL expression in whole-blood was CAD-risk-genotype-specific, and confirmed that low ANRIL was correlated with higher CDKN2B, but not CDKN2A expression. These data support recent studies implicating reduced ANRIL expression and reciprocal over-expression of CDKN2B, which is thought to impair TGFβ signalling, in CAD susceptibility.